(untitled) (Texas Journal of Philology, Culture and History, 2023)
One of the departments of linguistics is the department of phraseology. This department provides information about the phrasemes in the vocabulary of the language. A linguistic unit consisting of the combination of more than one independent lexeme, which has a figurative and spiritual nature, is called a phraseology: "The hair on the top stood on end, the vinegar does not hold water, etc."